2019
DOI: 10.3390/su11216041
|View full text |Cite
|
Sign up to set email alerts
|

How Do Trade-Offs and Synergies between Ecosystem Services Change in the Long Period? The Case Study of Uxin, Inner Mongolia, China

Abstract: Ecosystem services management should often expect to deal with non-linearities due to trade-offs and synergies between ecosystem services (ES). Therefore, it is important to analyze long-term trends in ES development and utilization to understand their responses to climate change and intensification of human activities. In this paper, the region of Uxin in Inner Mongolia, China, was chosen as a case study area to describe the spatial distribution and trends of 5 ES indicators. Changes in relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the one hand, the number of household members reflects the adequacy of labor force; household will increase their investment in land use to reduce their family burdens. For example, they increased mechanical power in artificial pasture or grazing pressure on nature grassland [39], which lead to an increase in the provisioning services and a decrease in the regulating services.…”
Section: Relationship Between Family Demographic Factors and Land Use...mentioning
confidence: 99%
“…On the one hand, the number of household members reflects the adequacy of labor force; household will increase their investment in land use to reduce their family burdens. For example, they increased mechanical power in artificial pasture or grazing pressure on nature grassland [39], which lead to an increase in the provisioning services and a decrease in the regulating services.…”
Section: Relationship Between Family Demographic Factors and Land Use...mentioning
confidence: 99%
“…In this study, driving forces were defined as factors leading to the observed quantitative and qualitative changes in ESs [ 13 , 14 ]. The main drivers that determine ES changes include the following types: climate change, land-use change, and socioeconomic factors [ 15 22 ]. As a global phenomenon, climate change is one of the most challenging issues of our time, with a tremendous impact on the provision of ESs by changing the biophysical structures and processes of the ecosystem [ 12 , 14 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ecosystem services do not have a main influence on partitioning results and have only been included as an accessory. Other studies have integrated several ecosystem services associated with soil and water conservation into the indicator system, such as soil formation and conservation [15,16]; however, as ecosystem tradeoffs exist, focusing on upgrading a certain ecosystem service could impair one or more other services, which could thus lead to a decline in unexpected ecosystem services [17][18][19]. For example, since 1999, the "Grain to Green" revegetation program has effectively increased soil formation and conservation on the semi-arid Loess Plateau in China, but it has also led to a decline in hydrological regulation and promoted water shortages for the population [20,21].…”
Section: Introductionmentioning
confidence: 99%